Flow Features of Thermophoretic MHD Viscous Fluid Flow Past a Converging Channel with Heat Source and Chemical Reaction - Kalita B.K. (International Journal of Applied Mechanics and Engineering, 2021)
A boundary layer flow of an electrically conducting viscous fluid past a converging channel in the presence of thermophoresis, heat source, chemical reaction, viscous dissipation and simultaneous heat and mass transfer characteristics is studied in the paper. An external magnetic field of uniform strength is applied transversely to the channel. The similarity solution has been used to transform the partial differential equations that represent the problem into a boundary value problem of coupled ordinary differential equations, which in turn are solved numerically using MATLAB’s built in solver bvp4c. Numerical computations are carried out to solve the problem and graphical illustrations are made to get the physical insight of the same. The convergent channel flow problem of an incompressible electrically conducting viscous fluid in the presence of a magnetic field has a wide range of applicability in different areas of engineering, specially in industrial metal casting and control of molten metal flow.